Analysis on the effectiveness of the gamification process - Koppolu, Sarath Chandra (2016)
Gamification is the concept of applying game-mechanics and design to the non-game context applications and process to make them more engaging and effective. This concept is still relatively new and is growing and evolving at a rapid pace and the success of this concept depends on all the game mechanics that are employed. This thesis aims at analyzing the effectiveness of the gamification process in the present day scenario. To analyze this, a qualitative in-depth research is done within a multi-national organization by conducting semi-structured interviews with participants from various functions and levels. It also gives a clear understanding on the concepts of gamification and also gives an in-depth review on all the elements such as mechanics, design, etc. that go into it and the measures of the effectiveness of the process with the help of various frameworks and studies that have already been done. By reviewing the literature and the analysis of the data from the interviews, recommendations and conclusions are drawn that would help understand how to make the gamification process effective in the present day scenario and also gives insights into future of gamification. Dissertation author: Sarath Chandra Koppolu Dissertation title: Analysis on the Effectiveness of the Gamification Process.